PERAN KREATIVITAS, INOVASI, DAN ORIENTASI PASAR DALAM MEMBENTUK KEUNGGULAN BERSAING KAFE FILOSOFI KOPI JOGJA - Radito, Th A; Daya, Ridha Zulfikri; Prapti, Meniek Srining (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This study examines the influence of creativity, innovation, and market orientation on competitive advantage. Research was conducted on consumers of Kafe Filosofi Kopi Jogja. The objects in this study are Creativity, Innovation, Market Orientation, and Competitive Advantage. The population in this study was all consumers of Kafe Filosofi Kopi Jogja who were buying at Kafe Filosofi Kopi Jogja. The sampling method used is purposive sampling with a sample of 200 respondents. The data was processed using multiple regression. The results showed that creativity, innovation, and market orientation have a significant influence on competitive advantage. Innovation proved to have the greatest influence (B coefficient value of 0.361) followed by creativity (B coefficient value of 0.267, and market orientation (B coefficient value of 0.262). The research model is proven to be able to explain the influence of Creativity, Innovation, and Market Orientation on competitive advantage (with an F value of 40.204 with a significance level of 0.000).